Flows of Chemical Risk Information in the Consumer Paint Product Chain. (14th January 2013) - Fransson, Kristin; Brunklaus, Birgit; Molander, Sverker
Summary In this study the flows of chemical risk information for paint as a consumer product were investigated from a product chain perspective. The main method of research involved semi‐structured interviews with Swedish manufacturers of paint and chemicals. In addition, retailers and consumers were interviewed. The flows of chemical risk information between actors within (e.g., manufacturers, retailers, and consumers) and outside (e.g., industry associations and regulators) the paint product chain are described. Because the European chemical legislation REACH (Registration, Evaluation, Authorization and restriction of CHemicals) plays a large role in the management of chemical risk information at companies, some consequences of REACH on actors in the paint product chain are described. Examples of such consequences are that importing of chemicals from non–European Union (EU) countries may be discouraged and that some low‐volume chemicals may no longer be produced. However, manufacturers do not yet see these consequences as impediments to innovation. The results of this work show that chemical risk information is most comprehensive during the manufacturing steps of the product chain. This is due not only to tradition and industry initiatives, but also to REACH and other legislation. The results also illustrate the need for evaluation of how chemical risk information is used in different contexts and the importance of directing the right information at the right target group. Following legislative development, more specialized information is required in the safety data sheet (SDS), and because of this many manufacturers find it necessary to create simplified safety sheets that make the most pertinent safety and hazard information easily accessible to individuals that handle the chemicals in their factories. The study found that in creating the simplified safety sheets, the content and use of chemical risk information is evaluated and adjusted for presentation to this particular target group. It is evident that the Swedish Paint and Printing Ink Makers Association plays an important role in the interpretation of legal requirements and even in agreements for providing information that exceeds legal requirements.